2005
DOI: 10.1007/s11010-005-4034-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of tumor associated antigen in mice exposed to a hepatocarcinogen

Abstract: The present investigation is aimed to identify and characterize tumor-associated antigen (TAA) in animals exposed to hepatocarcinogen. Swiss albino mice showed an enhanced expression of an approximately 58 kDa glycoprotein in liver cells upon exposure to a potential hepatocarcinogen N-nitrosodibutylamine (DBN). Carcinogenesis induction in mice was monitored by assays of y-glutamyl transpeptidase (GGT), acetylcholine esterase (AChE), glutathione-S-transferase (GST) activities and the level of glutathione (GSH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…DEN was administered by intravenous (i.v.) route[1112] at weekly intervals from week zero (start of the experiment) until the end of experiment (16 or 28 weeks). The exposures to the HPE (either AT or CC) were initiated from week 10 until the end of experiment (weeks 16 or 28) by thrice weekly intraperitoneal (i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…DEN was administered by intravenous (i.v.) route[1112] at weekly intervals from week zero (start of the experiment) until the end of experiment (16 or 28 weeks). The exposures to the HPE (either AT or CC) were initiated from week 10 until the end of experiment (weeks 16 or 28) by thrice weekly intraperitoneal (i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…The GGT assay was carried out by following the method described in our recent communication [8,9]. In brief, to 0.2 ml of γ -glutamyl-p-nitroanilide (0.005 M, pH 8.0) in a cuvette, 0.2 ml of glycylglycine (0.1 M, pH 8.0) and 0.6 ml of Tris-HCl buffer (0.1 M, pH 8.0) were added.…”
Section: γ -Glutamyl Transpeptidase (Ggt) Assaymentioning
confidence: 99%
“…Szemes and szamado (1991) found that rats received sodium nitrite showed histopathological changes in striated muscles, liver and kidney. Also, Alam et al (2005) observed that mice exposed to nitrosodibutylamine showed cell destruction and extensive necrosis.…”
Section: Introductionmentioning
confidence: 99%